Enhancement of Green Ghosts Due To Recurrence of Sprite Element - Xin Huang; Gaopeng Lu; Feifan Liu; Zhengwei Cheng; Frankie Lucena; Yu Liu; Xianghui Xue; Yongping Wang; Morris B. Cohen; Thomas Ashcraft; Paul Smith; Hank Schyma (Geophysical Research Letters)
Abstract We examined three observations of green emission events (labeled as event A, B and C, respectively) associated with red sprites as captured by amateurs. In all cases, the green emissions were recorded atop of red sprite. Based on the location of causative strokes and background star fields for events A and B, their altitudes are confined between 88 and 100 km, with the maximum brightness at 90.7 and 95.5 km, respectively. Events B and C were lit up for a second time after the recurrence of a sprite element, extending their duration to approximately 1,084 ms and 732.6 ms, much longer than that (about 500 ms) for event A; the intensity of green emissions was also enhanced due to sprite recurrence. It is inferred that the recurrence of sprite elements could affect the ambient condition by further increasing electron density and strengthening the electric field for the ghost production.